COLLISION CASCADE AND PRIMARY RADIATION DAMAGE IN SILICON CARBIDE: A MOLECULAR DYNAMICS STUDY - Ihda Husnayani; Muzakkiy Putra Muhammad Akhir (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
Silicon carbide (SiC) is a competitive candidate material to be used in several advanced and Generation-IV nuclear reactor designs as neutron moderator, fuel coating, cladding, or core structural material. Many studies have been performed to investigate the durability of SiC in severe environment in nuclear reactor. However, the nature and behavior of defect induced by neutron irradiation are still not fully understood. This paper is aimed to study collision cascade and primary radiation damage in SiC using molecular dynamics simulation. The potential being used was a hybrid Tersoff potential modified with Ziegler-Biersack-Littmark (ZBL) screening function. The collision cascade was let evolved for 10 ps from a Si or C primary knocked atom (PKA) located initially at the top center of a system containing 960.000 atoms. The simulation was carried out at room temperature as well as at several advanced fission reactor-relevant temperatures. It was obtained that the number of C point defects were larger than the number of Si point defects. The number of stable point defect was found to be temperature-dependent. It was also obtained that the recovery of point defects was larger at high temperature (>800 C).